Meeting the growing safeguards burden. Issue 5 (2nd September 2019) - Stewart, Ian J.; Mayhew, Noah
ABSTRACT: The International Atomic Energy Agency (IAEA) faces challenges in fulfilling its safeguards mandate as a result of an expanding safeguards burden and a relatively static budget. This dilemma has been exacerbated by the additional burdens of implementing the Joint Comprehensive Plan of Action (JCPOA) in Iran, but would not go away if implementation of the JCPOA were to end. There are three main areas of opportunity for the Agency: (1) budgetary expansion tied to changes in staffing policies, (2) changes in safeguards approaches, and (3) technological innovation. Barriers and limitations are associated with each approach, and advancing any of them will face a difficult political environment in Vienna.